An Empirical Segmentation of Users of Mobile Banking Apps. Issue 4 (1st October 2016) - Alavi, Shirin; Ahuja, Vandana
ABSTRACT: Digital technologies have squeezed the entire world into a small frame. Trade and transactions never stop, and they go where the customer is. Marketers must reinvent their strategies and toolkits to win in this hyper-connected world. Companies are creating new and improved ways for engaging and involving their consumers, and one significant tool now used by companies for these purposes is the app. Mobile phones have registered the highest growth among all technological evolutions, and mobile apps are proliferating. Apps are being used across a diverse range of industry verticals, including banking, e-commerce, travel, and tourism. This article studies a set of twenty different banking apps and segments consumers based on their adoption and usage of the apps. This article emphasizes the role of mobile technologies to change established channels and banking services, and also analyzes how the Indian banking sector has benefited from the adoption of mobile apps.